The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1055/s-0037-1598602
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertrophic Cardiomyopathy in Fetuses of Mothers with Gestational Diabetes before Initiating Treatment

Abstract: Objective To evaluate the prevalence of hypertrophic cardiomyopathy (HCM) in fetuses of pregnant women with gestational diabetes mellitus (GDM) in the beginning of the treatment. Methods A cross-sectional study was performed between July 1, 2013, and December 20, 2013, in a public maternity clinic in southern Brazil. The subjects were 63 fetuses of mothers with gestational diabetes, with a single pregnancy and no other associated pathologies. We diagnosed HCM through a fetal echocardiography before treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…15 Myocardial hypertrophy, as a result of fetal hyperglycemia and hyperinsulinism, is a frequent finding in the fetuses of diabetic mothers, which may lead to increased ventricular stiffness thereby affecting diastolic ventricular filling as well as systolic cardiac function. [16][17][18] It is well known that impairment of ventricular function may cause diastolic dysfunction first and subsequently lead to systolic dysfunction in children with heart diseases. However, data in the literature, evaluating specific systolic and diastolic parameters in fetuses, are varied due to variation in methods used by researchers to evaluate heart function.…”
Section: Discussionmentioning
confidence: 99%
“…15 Myocardial hypertrophy, as a result of fetal hyperglycemia and hyperinsulinism, is a frequent finding in the fetuses of diabetic mothers, which may lead to increased ventricular stiffness thereby affecting diastolic ventricular filling as well as systolic cardiac function. [16][17][18] It is well known that impairment of ventricular function may cause diastolic dysfunction first and subsequently lead to systolic dysfunction in children with heart diseases. However, data in the literature, evaluating specific systolic and diastolic parameters in fetuses, are varied due to variation in methods used by researchers to evaluate heart function.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of fetal hypertrophic myocardiopathy, conotruncal anomalies, ventricular septal defects, and other cardiac malformations is increased in mothers with DM and is associated with higher rates of perinatal morbidity and mortality. 2) 14) 15) The hypertrophy of IVS is the most common structural cardiac anomaly in fetuses from mothers with DM, and with a deleterious risk on the fetal heart function. In this scenario, several studies have been published including ultrasound/echocardiographic fetal cardiac functional parameters by M-mode, Doppler, 2D and 3D ultrasound in the fetuses of mothers with DM.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few works recently that examined the thickness of the interventricular septum (IVS), which separates the left and right ventricles, in FMH. Carolina et al [24] evaluated the prevalence of FMH in the fetuses of pregnant women with GDM, and they found that 54% of 63 fetuses tested positive for FMH on fetal echocardiography. Mohammed et al [25] employed five-dimensional (5D) fetal echocardiography for the diagnosis of prenatal fetal hypertrophic cardiomyopathy on three separate groups: healthy members, controlled diabetic mothers, and uncontrolled diabetic mothers.…”
Section: Introductionmentioning
confidence: 99%